Food selection of a generalist herbivore exposed to native and alien seaweeds. Issue 2 (April 2018) - Noè, Simona; Badalamenti, Fabio; Bonaviri, Chiara; Musco, Luigi; Fernández, Tomás Vega; Vizzini, Salvatrice; Gianguzza, Paola
Abstract: Understanding which factors influence the invasion of alien seaweed has become a central concern in ecology. Increasing evidence suggests that the feeding preferences of native herbivores influence the success of alien seaweeds in the new community. We investigated food selection of a generalist native grazer Paracentrotus lividus, in the presence of two alien seaweeds ( Caulerpa cylindracea and Caulerpa taxifolia var. distichophylla ) and two native seaweeds ( Dictyopteris membranacea and Cystoseira compressa ). Sea urchins were fed with six experimental food items: C. cylindracea, C. taxifolia var. distichophylla, a mixture of C. cylindracea and C. taxifolia var. distichophylla, D. membranacea, C. compressa and a mixture of D. membranacea and C. compressa . P. lividus ingested all the combinations of food offered, though it preferentially consumed the alien mixture, C. cylindracea and D. membranacea . The alien C. taxifolia var. distichophylla was consumed significantly less than the other food items and, interestingly, it was ingested in a greater amount when mixed with C. cylindracea than when on its own. This finding suggests that C. taxifolia var. distichophylla may become vulnerable to sea urchin grazing when it grows intermingled with C. cylindracea, which does not gain immediate protection from the presence of the very low palatable congeneric seaweed. The present study highlights the potential role of native grazers to indirectly affect the interspecific competition between the two alien seaweeds in the Mediterranean Sea. Highlights: Paracentrotus lividus avoided the new alien strain Caulerpa taxifolia var. distichophylla when offered by its own. The consumption of C. taxifolia var. distichophylla increased when it was mixed with Caulerpa cylindracea . C. taxifolia var. distichophylla may become vulnerable to sea urchin grazing when it grows intermingled with C. cylindracea .